Can perceived risks associated with a destination be moderated by organic and induced information sources? - Quintal, Vanessa; Roff, Elizabeth (Detay Anatolia Akademik Yayincilik Danismanlik Org. Turz. Ltd, 2012)
Information sources are critical to tourism decision-making as they reduce the risk prospective travellers perceive in making a destination choice. The current study examines two types of information sources. Organic sources are objective, third party information sources such as leisure books/guides/magazines. Induced sources are subjective, company-endorsed information sources that market a travel offering such as tourism office brochures. A 15-minute pen and paper questionnaire was self administered to 228 respondents at a shopping mall in Western Australia. Findings suggested that organic information sources such as leisure books/guides/magazines were consulted by significantly more respondents with lower perceived physical risk. On the other hand, induced information sources such as tourism office brochures were consulted by significantly more respondents with higher perceived physical risk.